2006
DOI: 10.1080/00365520510023909
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inflammatory markers in stools from patients with irritable bowel syndrome and collagenous colitis

Abstract: Increased levels of EPX, MPO and tryptase were observed in stools from collagenous colitis patients, whereas the levels in IBS patients did not differ from healthy controls. Our data suggest that faecal markers could be used as part of the clinical work-up to determine which patients should be biopsied and evaluated for collagenous colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
3
45
1
Order By: Relevance
“…Low-grade inflammation involving mast cells has previously been observed in some patients with IBS [14, 32]. However, in the present study, we failed to detect an increased local mast cell activity in the IBS patients as well as in most of the other patients.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Low-grade inflammation involving mast cells has previously been observed in some patients with IBS [14, 32]. However, in the present study, we failed to detect an increased local mast cell activity in the IBS patients as well as in most of the other patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Eosinophil protein X (EPX), one of the major proteins released by eosinophils [12], and tryptase, one of the major proteins released by mast cells during allergic reactions, can be accurately measured in feces [13, 14]. In a previous study including adult patients with food hypersensitivity, we observed an overall increase in the fecal levels of EPX (F-EPX) over time during periods of variable symptoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine assays have revealed no major changes in the basal levels of cytokines in IBS patients [31][32][33][34] with the exception of IL6 and IL8, which have been found to be moderately increased in some studies. 31,34,35 A decrease in the levels of the antiinflammatory cytokine IL10 has also recently been reported in children with IBS, 36 although this decrease was not observed in adults.…”
Section: Resultsmentioning
confidence: 99%
“…For example, eosinophil protein X (EPX), myeloperoxidase (MPO), tryptase, interleukin 1β or tumor necrosis factor α measured in supernatants from processed feces of patients with IBS were not elevated, in contrast to positive (IBD) controls. 6 Similarly, increased CD3 lymphocytes are observed in colonic biopsies. 7 or mast cells are increased in colonic or ileal biopsies in some studies; 8-10 however, other studies did not confirm these findings e.g., mast cell numbers are not increased in the colonic biopsies from patients with post-dysentery IBS.…”
Section: Introductionmentioning
confidence: 94%